Flypaper Effect dan Pembangunan Manusia di Jawa Tengah: Bukti Empiris dari Eks-Karesidenan Pekalongan - Haryono Haryono; Reza Susatyo; Fafurida Fafurida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The high dependence of the General Allocation Fund (DAK) on the Regional Budget (APBD) risks creating spending inefficiencies that directly impact the quality of human development. This study aims to detect the flypaper effect phenomenon and analyze the impact of fiscal decentralization on public welfare in seven regencies/cities in the former Pekalongan Residency for the 2020–2024 period. Using a panel data regression method with a Fixed Effect Model approach, this study tested two analytical models: Model 1 to detect the response of regional spending, and Model 2 to measure the impact of fiscal variables on the Human Development Index (HDI). The results of the analysis of Model 1 indicate that Regional Original Revenue (PAD) has a positive and significant effect on regional spending. The General Allocation Fund (DAU) has a positive but insignificant effect on regional spending. Evidence of the flypaper effect was found not to occur at the research locus, where there was no significant difference between the PAD coefficient and the DAU coefficient. In Model 2, PAD and DAU partially and simultaneously had a significant positive effect on the Human Development Index. This study recommends strengthening local taxing power through optimizing regional taxes and shifting the spending structure toward productive capital expenditure to improve fiscal independence and the quality of human development in a sustainable manner.